Предмет: Математика,
автор: matvei1231
номер 895 срочно пожалуйста
Приложения:

Ответы
Автор ответа:
0
(b-c)(b+c)-b+c=(b-c)(b+c-1)
(a+b)-(a+b)(a-b)=(a+b)(1-a+b)
(a-c)(a+c)-(a-c)=(a-c)(a+c-1)
(n-m)(n+m)-(n-m)=(n-m)(n+m-1)
(a+b)-(a+b)(a-b)=(a+b)(1-a+b)
(a-c)(a+c)-(a-c)=(a-c)(a+c-1)
(n-m)(n+m)-(n-m)=(n-m)(n+m-1)
Похожие вопросы
Предмет: Українська мова,
автор: victoriaguseva11
Предмет: Алгебра,
автор: Aleksandroval
Предмет: Алгебра,
автор: karakrosss
Предмет: Математика,
автор: ekurenkova
Предмет: Математика,
автор: 1984д6